Off the beaten track discovering the cross-cultural encounters of backpackers and locals in Sagada - Crisanto, Janine Marie Campilan 1991-; Pizarro, Anna Katrina Beltran; De Fiesta-Mateo, Florinda B.; University of the Philippines. College of Mass Communication (2013)
"This research study looked into backpacking tourism in Sagada, Philippines specifically in the context of cross-cultural communication. It incorporated concepts from the Coordinated Management of Meaning theory to discover the communication styles backpackers and locals used to deal with the cross-cultural situations they encountered in Sagada. Through qualitative research methods, a profile of Sagada, its locals and the backpackers, and a description of the extent of interaction between the two groups, the approaches used in cross-cultural situations and the evaluations of their experiences were created. Based on the study findings, the extent of interaction between the backpackers and locals existed in two levels: brief interactions which resulted into shallow relationships and prolonged interactions, both groups used verbal and non-verbal communication styles in employing different approaches, such as accomodation, avoidance, compromise and collaboration, to cope with the cultural differences between them. Thus, regardless of any conflicts encountered, both the backpackers and locals in Sagada found their tourism experiences to be positive."
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Backpacking -- Philippines -- Sagada; Intercultural communication -- Philippines; Cultural fusion; Tourists; Travellers